Morphology of Richards' gland in the wasp Metapolybia docilis - Billen, Johan; Noll, Fernando B. [UNESP] (My University, 2011)
Richards' gland in the epiponine wasp Metapolybia docilis occurs at the anterior side of the 5 th abdominal sternite, and is formed by approx. 360 secretory cells. The cells discharge their secretory products through accompanying duct cells into a reservoir that is formed by the invaginated intersegmental membrane between the 4 th and 5 th sternites. The ultrastructural characteristics of the secretory cells are indicative for the production of a non-proteinaceous secretion, which is in line with the trail substance that is used by these wasps during their swarm-founding.
Keywords: Epiponini; Exocrine glands; Histology; Ultrastructure